EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP/MTs DI KABUPATEN SRAGEN - Nyoto, Nyoto; Usodo, Budi; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of this research were to investigate: (1) which one had a better mathematics achievement, students instructed with the cooperative learning of Think Pair Share (TPS) type with Realistic Mathematics Education (RME) approach, the cooperative learning of TPS type, or the direct learning model; (2) which one had a better mathematics achievement, students who had visual learning style, auditorial learning style, or kinesthetic learning style; (3) on each type of learning model, which one had a better mathematics achievement, students who had visual learning style, auditorial learning style, or kinesthetic learning style; (4) on each learning style, which one had a better mathematics achievement, students instructed with the cooperative learning of TPS type with Realistic Mathematics Education approach, the cooperative learning of TPS type, or the direct learning model. This research was quasi experimental with 3Ã3 factorial design. The population was all students of the grade VIII State Junior High Schools/Islamic State Junior Secondary School in Sragen Regency. Sampling was done by stratified cluster random sampling technique. The sample consisted of 308 students. The instrument used to collect data was mathematics achievement test and questionnaire of students learning style. Balance test used unbalanced one way analysis of variance. The hypothesis test used unbalanced two ways analysis of variance at the significance level of 0,05. Based on hypothesis test, it can be concluded as follows. (1) Students intructed with the cooperative learning model of TPS type with RME approach had the same mathematics achievement as students intructed with the cooperative learning model of TPS type. Students intructed with the cooperative learning model of TPS type with RME approach and the cooperative learning model of TPS type had better mathematics achievement than students intructed with the direct learning model. (2) Students with visual learning style had the same mathematics achievement as students with auditorial learning style. Students with visual learning style had better mathematics achievement than student with kinesthetic learning style, and students with auditorial learning style had the same mathematics achievement as students with kinesthetic learning style. (3) On the cooperative learning model of TPS type with RME approach, the cooperative learning model of TPS type, and the direct learning model, students with visual learning style had the same mathematics achievement as students with auditorial learning style. Students with visual learning style had better mathematics achievement than student with kinesthetic learning style, and students with auditorial learning style had the same mathematics achievement as students with kinesthetic learning style. (4) On students with visual learning style, auditorial learning style, and kinesthetic learning style, students intructed with the cooperative learning model of TPS type with RME approach had the same mathematics achievement as students intructed with the cooperative learning model of TPS type. Students intructed with the cooperative learning model of TPS type with RME approach and the cooperative learning model of TPS type had better mathematics achievement than students intructed with the direct learning model.Keywords: TPS, RME, students learning style